2015
DOI: 10.4103/0250-474x.159596
|View full text |Cite
|
Sign up to set email alerts
|

Role of components in the formation of self-microemulsifying drug delivery systems

Abstract: Gurram, et al: Pharmaceutical Excipients of Self-microemulsifying Drug Delivery SystemsPharmaceutical research is focused in designing novel drug delivery systems to improve the bioavailability of poorly water soluble drugs. Self-microemulsifying drug delivery systems, one among the lipid-based dosage forms were proven to be promising in improving the oral bioavailability of such drugs by enhancing solubility, permeability and avoiding first-pass metabolism via enhanced lymphatic transport. Further, they have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…The two most commonly reported mechanisms of nanoemulsion formation from SNEDDS are diffusion of the hydrophilic co-solvent or co-surfactant from the organic phase into the aqueous phase (Pouton, 2000; Solans and Solé, 2012; Solè et al, 2012), and formation of nanoemulsion negative free energy at transient negative or ultra-low interfacial tensions (Agrawal et al, 2012; Gurram et al, 2015; Kohli et al, 2010). SNEDDS are also the most popular and promising tool for delivery of hydrophobic drugs with low bioavailability (Meena et al, 2012; Patel and Vavia, 2007; Patel et al, 2016; Suryawanshi and Kondawar, 2014).…”
Section: Formulation Techniques Of Nanoemulsion Drug Delivery Systemsmentioning
confidence: 99%
“…The two most commonly reported mechanisms of nanoemulsion formation from SNEDDS are diffusion of the hydrophilic co-solvent or co-surfactant from the organic phase into the aqueous phase (Pouton, 2000; Solans and Solé, 2012; Solè et al, 2012), and formation of nanoemulsion negative free energy at transient negative or ultra-low interfacial tensions (Agrawal et al, 2012; Gurram et al, 2015; Kohli et al, 2010). SNEDDS are also the most popular and promising tool for delivery of hydrophobic drugs with low bioavailability (Meena et al, 2012; Patel and Vavia, 2007; Patel et al, 2016; Suryawanshi and Kondawar, 2014).…”
Section: Formulation Techniques Of Nanoemulsion Drug Delivery Systemsmentioning
confidence: 99%
“…Interestingly, another potential topical/transdermal drug delivery angle can be to utilise the lipophilic nature of SEDDSs to reach lymph nodes located within the epidermis and dermis in order to further refine targeting of dermal drug delivery systems [44,45]. Lymphatic uptake of oral SEDDSs demonstrated successful avoidance of hepatic metabolism as well as increased drug bioavailability [33,46,47]. Therefore, similar advantages can potentially be created by dermal As indicated in Figure 1, there are three different skin penetration pathways by which drugs can cross the SC, namely, the transcellular-, transappengeal-, and intercellular pathways [36].…”
Section: Skin a Multi-layered Organmentioning
confidence: 99%
“…Interestingly, it was found that, due to increased solubility of highly lipophilic drugs in SEDDS formulations, less of the said drug is essential in order to obtain equivalent therapeutic effects [33]. Moreover, hepatic metabolism, which normally portrays a high affinity for lipophilic drug entities, is circumvented, since SEDDSs disperse into fine droplets within the aqueous environment of the gastrointestinal tract and are also lymphatically absorbed prior to hepatic exposure [33,46,47]. Thus, decreased drug concentrations in these delivery systems still render an appropriate therapeutic response due to the solubilisation as well as protection provided by the SEDDS vehicle [33].…”
Section: Active Compounds Incorporated In Seddssmentioning
confidence: 99%
“…Nankervis et al 33 demonstrated the effectiveness of linoleic acid and cottonseed oil (Long chain lipids) for enhancing the lymphatic absorption of retinoids over Miglyol 812, (medium-chain lipid) the latter though were less sensitive to oxidation and have comparatively higher solvent capacity. [34][35][36][37][38] Oral administration has always been attempted largely as compared with other routes considering potential benefits of patient's compliance and cost effectiveness. But oral anti-cancer drug access to systemic circulation and at the target site suffers from multitude of factors like poor aqueous solubility, extensive pre-systemic metabolism, efflux transporter activity, and these all factors collectively accounts for resistance against anti-cancer drugs.…”
Section: Lymphatic Transport Of Lipid Productsmentioning
confidence: 99%